O direito à propriedade privada e seus limites em John Locke - Ottonicar, Flavio Gabriel Capinzaiki (2025)
The limit to the right to private property is a too much discussed question in Locke’s thought. It is possible to state that this theme divided Locke's interpreters into two main groups: those who believe Locke defended the unlimited right to private property and those who, on the other hand, tried to show that Locke defended the limited right to private property. This work aims to demonstrate that the right to private property for Locke is only established when limited to conditions of a moral and political-legal nature, examining these conditions both in the state of nature and in the political state. To this end, we intend to highlight the restrictions suggested by Locke himself to the right to private property: restriction against waste, and to leave enough and as good for others and the natural human incapacity to appropriate considerable amount of land so as to not to leave enough and as good for others, in the context of initial state of nature, in which there is much more land available than individuals to appropriate it. With the invention of money and the emergence of the State, these conditions change. On the one hand, with the introduction of money, restrictions are reconfigured, as utility changes and appropriation capacity expands. On the other hand, the territorial delimitation inherent in the constitution of the State now restricts the amount of land available, which changes the requirement to leave so much land available and of such good quality that “enough” is left for the conservation of each of the others. Thus, based on the articulation between the foundations of the right to private property and its restrictions, and the role of money and the political State within the scope of these relations, we intend to offer more evidence and corroborate the thesis that for Locke the right to private property is only established when circumscribed by conditions of a clearly limiting nature to this right.